System Failure Analysis Using FTA, LOPA, And Aspen HYSYS Approaches: The 2005 BP Texas City Case Study - Lucky Yudanto Anggoro; Fauzul Azmi; Agrytia Rut Meiriski Aritonang; Favian Hafiz Zain; Bani Isnain Rochmatan Imannudin; Selly Purwasi; Eka Fitriani Ahmad (CV. AFDIFAL MAJU BERKAH, 2026)
This research aims to comprehensively analyze the 2005 BP Texas City accident by integrating Fault Tree Analysis (FTA), Layers of Protection Analysis (LOPA), and Aspen HYSYS conceptual simulation. Using a qualitative descriptive approach, this study reconstructs systemic failures based on official investigation reports. FTA results reveal complex interactions between instrumentation failures, operational deviations, and design weaknesses as primary causes, while LOPA evaluation demonstrates the ineffectiveness of all independent protection layers in preventing hazard escalation. Furthermore, Aspen HYSYS simulation visualizes the dynamics of mass and energy imbalance during the start-up phase leading to column overfilling. This research contributes significantly to the development of process safety education by providing an integrated risk analysis framework to understand the evolution of industrial accidents holistically. The practical implications emphasize the urgency of implementing inherently safer designs, improving start-up management, and strengthening safety culture to prevent the recurrence of catastrophic incidents in the future.